Histone deacetylase activity modulates alternative splicing - Hnilicová, Jarmila; Hozeifi, Samira; Dušková, Eva; Icha, Jaroslav; Tománková, Tereza; Staněk, David (PLoS One, 2011)
There is increasing evidence to suggest that splicing decisions are largely made when the nascent RNA is still associated with chromatin. Here we demonstrate that activity of histone deacetylases (HDACs) influences splice site selection. Using splicing-sensitive microarrays, we identified ∼700 genes whose splicing was altered after HDAC inhibition. We provided evidence that HDAC inhibition induced histone H4 acetylation and increased RNA Polymerase II (Pol II) processivity along an alternatively spliced element. In addition, HDAC inhibition reduced co-transcriptional association of the splicing regulator SRp40 with the target fibronectin exon. We further showed that the depletion of HDAC1 had similar effect on fibronectin alternative splicing as global HDAC inhibition. Importantly, this effect was reversed upon expression of mouse HDAC1 but not a catalytically inactive mutant. These results provide a molecular insight into a complex modulation of splicing by HDACs and chromatin modifications.
Keywords: Animals; HeLa Cells; Nuclear Proteins; Histone Deacetylases; jaderné proteiny; inhibitory histondeacetylas; transfekce; proteiny vázající RNA; Transfection; lidé; HeLa buňky; Histone Deacetylase 1; Mice; histondeacetylasy; stanovení celkové genové exprese; kultivované buňky; myši; Histone Deacetylase Inhibitors; regulace genové exprese; Cells, Cultured; mikročipová analýza; RNA-Binding Proteins; Microarray Analysis; alternativní sestřih; Gene Expression Regulation; zvířata; Alternative Splicing; histondeacetylasa 1; Gene Expression Profiling; Humans